Emotion Regulation and Intimate Partner Violence Perpetration in Undergraduate Samples: A Review of the Literature. (April 2023) - Neilson, Elizabeth C.; Gulati, Natasha K.; Stappenbeck, Cynthia A.; George, William H.; Davis, Kelly Cue
Intimate partner violence (IPV) perpetration increases throughout young adulthood and is particularly widespread among college students, resulting in mental health and academic consequences. Deficits in emotion regulation (ER) are an important factor associated with IPV perpetration; the developmental tasks and challenges associated with college, including relationship stressors and hazardous alcohol use, implicate ER as a particularly relevant risk factor for IPV perpetration. Thus, college presents an important opportunity for intervention in order to change the trajectories of IPV perpetration across young adulthood. The purpose of this review was to synthesize findings regarding ER and psychological, physical, and sexual IPV perpetration among college students. Twenty-one articles met inclusion criteria. Studies were organized into five categories: (a) direct associations of ER with IPV perpetration, (b) qualitative assessment of ER and IPV, (c) ER in indirect effects models, (d) ER in moderation models, and (e) experiments with ER instructional sets. Overall, ER emerged as an important inhibiting factor for IPV perpetration, particularly impulse control and access to ER strategies. ER deficits in the context of impelling (e.g., negative affect, trauma history) and instigating (e.g., provocation) factors emerged as consistent predictors of psychological and physical IPV perpetration for both male and female students. Deficits in ER were associated with sexual IPV perpetration among men; however, very few studies examined sexual IPV. Experimental paradigms suggest cognitive reappraisal may reduce IPV perpetration, while suppression may, in some contexts, increase perpetration. Methodological strengths and weaknesses and implications for IPV prevention and interventions programming for college students are discussed.